The treatment of spinal cord injury: past, present and future - Fawcett, James (Henry Stewart Talks, 2012)
Spinal cord injury, History of spinal cord injury research, Needs of spinal injury patients, Reproduction and sexual function, Bladder function, Neuroprotection, Axon regeneration, Plasticity, Reactivation of plasticity, Combined plasticity and rehabilitation, Electronic restoration of function, Clinical threshold for repair treatments